2004
DOI: 10.1016/j.vetpar.2004.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of an optimized dog-culling program in the dynamics of canine Leishmania transmission

Abstract: In Brazil, zoonotic visceral leishmaniasis (ZVL) control programs based on the mass elimination of seropositive dogs have failed to reduce the number of leishmaniasis cases. However, these programs have been done under sub-optimal conditions. We studied a cohort of dogs in an urban area in Brazil to determine, whether a dog-culling program optimized with: (i) replacement of a relatively low-sensitivity indirect immune-fluorescent test on blood eluate by a more sensitive enzyme-linked immunosorbent assay on ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0
13

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(71 citation statements)
references
References 17 publications
0
56
0
13
Order By: Relevance
“…Their main questions were regarding the diffi culties observed in most municipalities and were related to the problem of asymptomatic dogs; infections in these animals are generally not detected and contribute to the maintenance of the disease cycle. Furthermore, Moreira Jr et al 24 suggested problems related to the low stability and sensitivity of the assays used to detect the infection in dogs, the long period between diagnosis and canine euthanasia, the resistance of the owners in relation to the euthanasia procedure, and the rapid replacement of the dogs.…”
Section: Vlh Cases -1999 To 2012mentioning
confidence: 99%
“…Their main questions were regarding the diffi culties observed in most municipalities and were related to the problem of asymptomatic dogs; infections in these animals are generally not detected and contribute to the maintenance of the disease cycle. Furthermore, Moreira Jr et al 24 suggested problems related to the low stability and sensitivity of the assays used to detect the infection in dogs, the long period between diagnosis and canine euthanasia, the resistance of the owners in relation to the euthanasia procedure, and the rapid replacement of the dogs.…”
Section: Vlh Cases -1999 To 2012mentioning
confidence: 99%
“…15 The results of several intervention studies based on serological screening of dogs and killing of seropositive animals are equivocal. [16][17][18][19][20] In theory, effective control would require a high proportion of infectious dogs to be removed immediately upon detection to achieve a marked reduction in disease transmission. 8,9 Thus, it is postulated that if culling could target infectious (rather than simply infected) dogs, its effectiveness may be increased because the proportion of dogs that have never been infectious in the population may increase.…”
Section: Introductionmentioning
confidence: 99%
“…Entretanto, a correlação entre casos caninos e humanos apresentou-se negativa (r= -0,0388) indicando que a presença de cães infectados não é um fator determinante para o aparecimento da doença em humanos no município de Fortaleza. Além disso, a prática da eutanásia de animais soropositivos não vem diminuindo a prevalência da infecção em humanos (Moreira et al 2004). Este fato corrobora com um estudo de intervenção controlado onde foi sugerido que a eliminação de cães soro reagentes pode afetar a incidência cumulativa de LVC e temporariamente pode também diminuir a incidência de casos da LV em humanos, embora a transmissão continue após a remoção dos cães o que sugere a presença de outros reservatórios (Da Silva et al 2010, Helhazar et al 2013.…”
Section: Discussionunclassified